3D MODELING, SIMULATION AND ANALYSIS OF ANTI-VIBRATION BORING BAR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This study presents the capabilities of the engineering dynamic analysis according to the Finite Elements Method (FEM), demonstrated on a 3D virtual prototype of a part "Anti-vibration boring bar" for lathe. The analysis is performed with help of CAE system Ansys. The modal frequencies are determined which are necessary for optimizing the constructive parameters of the product during the design stage.